NEW DATA ON AMMONOIDS AND BIOSTRATIGRAPHY OF THE CLASSICAL SPATHIAN KÇIRA SECTIONS (LOWER TRIASSIC, ALBANIA) (Rivista italiana di Paleontologia e Stratigrafia, 2018)
New bed-by-bed data on ammonoids and their stratigraphic position within three sections from the Lower and Middle Triassic Han-Bulog Limestone of Kçira (Northern Albania) are presented. Two of the sections studied are most likely from the classical localities described by Nopcsa in 1929. They have pro vided the only two ammonoid collections known from the Albanian Lower Trias, which are known as Arthaber's and Nopcsa's collections, now stored in Wien and London, respectively. The ammonoids from the two collections, although sampled discontinuously (not bed-by-bed), supplied the base of a substantial part of the Spathian taxonomy in the Western Tethys. The new sampling of the basal portion of the Han-Bulog Limestone of Kçira pro vided the layers with the richest and most diversified faunas. Two marker levels recognized within the lowest 2.5 m of the succession are characterized by the acme of the genus Subcolumbites, that is practically absent in the middle-higher part of the formation. These basal faunas were assigned to the Subcolumbites-Prohungarites Oppel zone, whose local revision is suggested with the introduction of the taxon range zone "Subcolumbites beds". The middle portion of the Han-Bulog Limestone pro vided only small long-ranging ammonoids belonging to the genera Procarnites, Leiophyllites and Eophyllites. Scant faunas with long-ranging Anisian forms (Procladiscites, Sturia, Proarcestes, Monophyllites) were found at the top of the succession within isolated blocks.